2016
DOI: 10.1177/1753425916632303
|View full text |Cite
|
Sign up to set email alerts
|

L-Cysteine protects intestinal integrity, attenuates intestinal inflammation and oxidant stress, and modulates NF-κB and Nrf2 pathways in weaned piglets after LPS challenge

Abstract: In this study we investigated whetherL-cysteine (L-cys) could alleviate LPS-induced intestinal disruption and its underlying mechanism. Piglets fed with anL-cys-supplemented diet had higher average daily gain.L-cys alleviated LPS-induced structural and functional disruption of intestine in weanling piglets, as demonstrated by higher villus height, villus height (VH) to crypt depth (CD) ratio, and transepithelial electrical resistance (TER) and lower FITC-dextran 4 (FD4) kDa flux in jejunum and ileum. Supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 37 publications
(71 reference statements)
1
65
0
Order By: Relevance
“…This raised the possibility of a complex chronology of inflammatory signaling in skeletal muscle occurring earlier in the response to environmental hyperthermia. LPS can activate inflammatory signaling (Song et al 2016) and endotoxemia appears to be a consistent effect of heat stress (Pearce et al 2012(Pearce et al , 2013a. Moreover, we found recently that 12 h of heat stress led to oxidative stress and that it has long been appreciated that oxidative stress can promote inflammatory signaling (Ambade and Mandrekar 2012).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This raised the possibility of a complex chronology of inflammatory signaling in skeletal muscle occurring earlier in the response to environmental hyperthermia. LPS can activate inflammatory signaling (Song et al 2016) and endotoxemia appears to be a consistent effect of heat stress (Pearce et al 2012(Pearce et al , 2013a. Moreover, we found recently that 12 h of heat stress led to oxidative stress and that it has long been appreciated that oxidative stress can promote inflammatory signaling (Ambade and Mandrekar 2012).…”
Section: Introductionmentioning
confidence: 84%
“…LPS can activate inflammatory signaling (Song et al. 2016) and endotoxemia appears to be a consistent effect of heat stress (Pearce et al. 2012, 2013a,c).…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that LPS induces acute bacterial infection, followed by stimulating macrophages and monocytes to produce and secrete related pro-inflammatory cytokines, eventually leading to organism systemic inflammation. 29 Consistent with improved intestinal integrity, dietary Cu/Zn-Mt decreased pro-inflammatory cytokine expression (TNF-a, IL-1b, IL-6, and IL-8), which indicated that LPS-induced inflammation was minimized by Cu/Zn-Mt supplementation. Similar to our findings, Namkung et al 28 reported that dietary addition of Zn and Cu could help maintain homeostasis and immune function in weaned pigs after LPS challenge.…”
Section: Discussionmentioning
confidence: 85%
“…In this scenario, it is plausible that l-cysteine supplementation exhibits beneficial effects on corneal integrity by preventing an excessive oxidative state due to PRK surgery and thus by reducing the epithelial prolonged inflammation it favors a faster stromal recovery. In fact, it is well established the role of cysteine in alleviating intestinal inflammation and oxidative stress through the inhibition the NF-κB and the activation of the Nrf2 signaling pathways [36], which modulates the proliferation of epithelial cell. Similarly, it is well known that the activation of NF-kB pathway is involved in corneal inflammation [37], which could justify the beneficial effects of l-cysteine on corneal regeneration.…”
Section: Discussionmentioning
confidence: 99%